THE FOUNDATION OF CURRICULUM RENEWAL (REVIEWING FROM PHILOSOPHICAL, JURIDIC, HISTORICAL, PSYCHOLOGICAL, SOCIAL AND CULTURAL ASPECTS) - Hadi, Mokhamad Yaurizqika (Penerbit Widina, Widina Media Utama, 2022)
One of the important aspects in education is paying attention to the curriculum. The curriculum is an activity that includes various student activities in detail with a view to achieving educational goals. The curriculum will always evolve to meet the needs of an institution. When the curriculum is not developed in accordance with the increasing needs of an institution, the institution will be left behind. Curriculum preparation requires a strong foundation, which is based on the results of in-depth thinking and research and is in line with the challenges of the times. Because the curriculum is like a house that must have a foundation so that it can stand upright, not fall and can provide comfort for those who inhabit it, the foundation is a philosophical, juridical, psychological, social and cultural foundation. This study uses a library research approach. The technique in this research is to document in the form of data related to variables in the form of notes, books, journals and other articles. Furthermore, inductive data analysis is carried out, namely taking a conclusion or conclusion from a concrete situation leading to abstract things.ABSTRAKSalah satu aspek penting dalam pendidikan adalah memperhatikan kurikulum. Kurikulum merupakan suatu kegiatan yang mencakup berbagai kegiatan siswa secara terperinci dengan maksud untuk mencapai tujuan pendidikan. Kurikulum akan selalu berkembang untuk memenuhi kebutuhan suatu institusi. Ketika kurikulum tidak dikembangkan sesuai dengan kebutuhan yang semakin meningkat dari suatu lembaga, maka lembaga tersebut akan tertinggal. Penyusunan kurikulum memerlukan landasan yang kuat, yang didasarkan pada hasil pemikiran dan penelitian yang mendalam dan sesuai dengan tantangan zaman. Karena kurikulum ibarat sebuah rumah yang harus memiliki pondasi agar dapat berdiri tegak, tidak roboh dan dapat memberikan kenyamanan bagi yang menempatinya, pondasi tersebut adalah pondasi filosofis, yuridis, psikologis, sosial dan kultural. Penelitian ini menggunakan pendekatan penelitian kepustakaan (library research). Teknik dalam penelitian ini adalah dengan mendokumentasikan berupa data-data yang berhubungan dengan variabel yang berupa catatan, buku, jurnal dan artikel-artikel lainnya. Selanjutnya dilakukan analisis data secara induktif, yaitu mengambil suatu kesimpulan atau konklusi dari keadaan yang konkrit menuju kepada hal-hal yang abstrak.